Decolonizing English Language Teaching in the Philippines: A Literature Review - Tundag, Leian; G, Casquejo Kisha Erika; M, Siroy Daphne Joyce; T, Minoza Joemar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This literature review critically examines the colonial roots and contemporary realities of English Language Teaching (ELT) in the Philippines. Using a qualitative, critical-interpretive approach grounded in decolonial and postcolonial frameworks, this study synthesizes research on language policy, sociocultural perceptions, and pedagogical reforms, such as Mother Tongue-Based Multilingual Education (MTB-MLE). Findings reveal that English remains dominant and cannot be easily displaced due to its colonial legacy and association with socioeconomic mobility. Despite MTB-MLE's potential to affirm linguistic diversity, challenges persist due to entrenched attitudes and limited resources. Emerging decolonial strategies, including translanguaging and culturally sustaining pedagogy, offer promising avenues but face institutional barriers. This review contributes to ongoing dialogues on linguistic justice and the reimagining of ELT toward more equitable and culturally responsive education in the Philippine context.